Cost Effective Scheduling In MIMO Empowered Cognitive Radio Ad Hoc Networks (International Journal of Scientific Research and Management (IJSRM), 2015)
Multiple-input multiple-out (MIMO) and cognitive radio (CR), can both effectively participate in the transmission interference among links and thus increase the network throughput in wireless communications. The goal of this work is to develop a distributed algorithm that can concurrently exploit the agility of CR and MIMO to benefit from both the opportunities of spare spectrum channels and spatial degree of freedom (DoF) for an overall higher throughput and lower delay in a multi-hop wireless network. In this paper, here propose a jointly optimized relay selection scheme for by primary users (PUs), and the frequency bands unused by primary users (PUs) are sensed and assigned to secondary users (SUs)., aiming to reduce the computational burden of the selection procedure. Hence, it is possible to select an optimum relay with only one selection algorithm for two scheduling of PUs and SUs tasks